Anti-Lipid IgG Antibodies Are Produced via Germinal Centers in a Murine Model Resembling Human Lupus - Wong-Baeza, Carlos; Reséndiz-Mora, Albany; Donis-Maturano, Luis; Wong-Baeza, Isabel; Zárate-Neira, Luz; Yam-Puc, Juan Carlos; Calderón-Amador, Juana; Medina, Yolanda; Wong, Carlos; Baeza, Isabel; Flores-Romo, Leopoldo (Frontiers in Immunology, 2016)
Anti-lipid IgG antibodies are produced in some mycobacterial infections and in certain autoimmune diseases (such as anti-phospholipid syndrome, systemic lupus erythematosus). However, few studies have addressed the B cell responses underlying the production of these immunoglobulins. Anti-lipid IgG antibodies are consistently found in a murine model resembling human lupus induced by chlorpromazine-stabilized non-bilayer phospholipid arrangements (NPA). NPA are transitory lipid associations found in the membranes of most cells; when NPA are stabilized they can become immunogenic and induce specific IgG antibodies, which appear to be involved in the development of the mouse model of lupus. Of note, anti-NPA antibodies are also detected in patients with systemic lupus erythematosus and leprosy. We used this model of lupus to investigate in vivo the cellular mechanisms that lead to the production of anti-lipid, class switched IgG antibodies. In this murine lupus model, we found plasma cells (Gr1-, CD19-, CD138+) producing NPA-specific IgGs in the draining lymph nodes, the spleen, and the bone marrow. We also found a significant number of germinal center B cells (IgD-, CD19+, PNA+) specific for NPA in the draining lymph nodes and the spleen, and we identified in situ the presence of NPA in these germinal centers. In contrast, very few NPA-specific, extrafollicular reaction B cells (B220+, Blimp1+) were found. Moreover, when assessing the anti-NPA IgG antibodies produced during the experimental protocol, we found that the affinity of these antibodies progressively increased over time. Altogether, our data indicate that, in this murine model resembling human lupus, B cells produce anti-NPA IgG antibodies mainly via germinal centers.